The Analysis of Word Formation Processes in CNN News Political Articles - Swarniti, Ni Wayan (Humanis, 2024)
Morphological analysis typically consists of the identification of parts of words or more technically, constituents of words. The purpose of this research is to classify and analyze the process of word formation, especially derivational morphemes in political articles posted on the CNN News online news platform. The researcher used a qualitative research method. Data collecting technique used was observation. The results of the analysis were explained in detail. Results of the analysis was 11 suffixes found that classified as adjective derivation, 15 suffixes were identified as noun derivation, 5 suffixes was classified as verb derivation, and affixes that have function to change the meaning of word was 16 prefixes and 5 suffixes. The highest number of affixes found was affixes that have function to change the meaning of word. It meant that it prefer to use simple and effective words to make the readers easy to understand and more interested in reading another news in CNN News especially political articles.